2002
DOI: 10.1017/s1742758400015022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Development and Population Growth of an Exotic Stemborer, Chilo partellus (Swinhoe), and an Ecologically Similar Congener, C. orichalcociliellus (Strand) (Lepidoptera: Crambidae)

Abstract: Studies were conducted to determine the effect of temperature and diet on the development of Chilo partellus (Swinhoe) and Chilo orichalcociliellus (Strand) (Lepidoptera: Crambidae). Developmental times of C. partellus and C. orichalcociliellus for the egg, larval and egg -adult life stages were inversely related to temperature. The larval developmental period of C. orichalcociliellus reared on artificial diet was longer than the developmental period on natural diet. Chilo partellus had a higher intrinsic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
4
13
1
Order By: Relevance
“…In East and Austral Africa stem borer pests are frequently found as a community of species involving the two African noctuids and the invasive crambid pest Chilo partellus (Swinhoe). Comparison of the noctuid life table parameters presented in this study with those of the crambid (Singh, ; Mbapila et al, ; Khadioli et al . in press) shows that the intrinsic rate of increase of the crambid was twice as high within the range 20–31°C, with an optimum within 28–31°C.…”
Section: Discussionmentioning
confidence: 88%
“…In East and Austral Africa stem borer pests are frequently found as a community of species involving the two African noctuids and the invasive crambid pest Chilo partellus (Swinhoe). Comparison of the noctuid life table parameters presented in this study with those of the crambid (Singh, ; Mbapila et al, ; Khadioli et al . in press) shows that the intrinsic rate of increase of the crambid was twice as high within the range 20–31°C, with an optimum within 28–31°C.…”
Section: Discussionmentioning
confidence: 88%
“…As a result of its short life cycle, C. partellus may have more generations per year, as well as rapid population growth, suggesting its likely dominance over other stemborer species. Furthermore, the short generation time of C. partellus may confer the species with a superior competitive advantage over its competitors through its higher potential rate of increase (Kfir, ; Mbapila et al ., ; Dejen et al ., ) and rapid development (Reitz & Trumble, ), which may possibly give it a numerical advantage (Sujay et al ., ). Up to six generations of C. partellus can occur per year (Panwar, ) and this may be even higher given the increase in mean temperatures with global change.…”
Section: Competitive Displacement Of Indigenous Stemborer Speciesmentioning
confidence: 97%
“…This confers a survival and comparative advantage of C. partellus on key behavioural traits relative to other indigenous stemborer species. Previous studies reported a mean development time of approximately 48 days (25 °C) for C. partellus reared on artificial diet (Mbapila et al ., ; Khadioli et al ., ). However, the total developmental time of B. fusca was 72.56 and 52.6 days, respectively, at 25 and 26–30 °C (Khadioli et al ., ; Glatz et al ., ) and that of S. calamistis was 64.81 days at 25 °C (Table ) (Khadioli et al ., ).…”
Section: Competitive Displacement Of Indigenous Stemborer Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, maize stem borers accounts for 13.5% annual losses, but damage depends on the maize variety and the stage of attack (De Groote, 2002). Chilo partellus Swinhoe (Lepidoptera: Crambidae), a highly invasive stem borer, has become the most important maize stem borer in Kenya since its introduction in the 1930s (Mbapila, Overholt, & Kayumbo, 2002). In a stem borer distribution study done in Kenya, about 54 % of the recovered larvae were C.partellus Swinhoe (Crambidae), 40% Busseola fusca (Fuller) (Noctuidae), 4% Sesamia calamistis Hampson (Noctuidae) and 1% Chilo orichalcociliellus (Strand) (Crambidae), the rest were minor borer species (Ong'amo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%